European Settlement and the Making and Unmaking of Aboriginal Identities - Merlan, Francesca (The Australian journal of anthropology, 2006)
This paper explores variation and change in Aboriginal people's connections to places, and place-related identity, as a function of their differential historical relationship to a town. Among Aboriginal people who have lived for some decades in camps around Katherine, Northern Territory, descendants of those who appear to have the most clearly discernable long-term relationship with the area in the vicinity of the town do not relate to places, nor conceptualise them, in stereotypically ‘traditional’ terms. Their relationships to town and nearby places tend to be of an ideologically unelaborated, homely sort. Kinds of territorial relationships their antecedents can be shown to have had to the area have undergone dissolution. The paper seeks to develop discussion of such variation and the historical and sociological processes involved. The Katherine case brings the social and historical significance of ‘towns’ as sites of Aboriginal/non-Aboriginal interrelationship into focus, and also requires a critical view of notions of ‘group’ that have tended to dominate recent public process and understanding in Australia.